Engineering chronological lifespan toward a robust yeast cell factory - Zulin Wu; Jiaoqi Gao; Ning Gao; Yunxian Zhao; Yongjin J. Zhou (Proceedings of the National Academy of Sciences, 2025)
Metabolic rewiring helps to construct efficient microbial cell factories; however, these cells suffer from metabolic stress during long-term fed-batch fermentation. Thus, the construction of robust cells is vital for industrial application of microbial cell factories at the laboratory scale. Here, we systematically characterized longevity factors and pathways for biosynthesis of the diterpenoid sclareol and found that weakening nutrient-sensing pathways and enhancing mitophagy synergistically improved sclareol production by 70.3% (20.1 g/L with a yield of 0.046 g/g glucose). Further enhancing central metabolism improved sclareol production to 25.9 g/L with a yield of 0.051 g/g glucose, the highest production achieved in microbes. Omics data demonstrated that the extension of chronological lifespan by upregulating the expression of lifespan-related genes automatically remodeled the cellular metabolism and improved overall cellular robustness for efficient chemical biosynthesis. We also showed that our strategy significantly improved the biosynthesis of other products such as sesquiterpene β-elemene and phenolic acids. Therefore, this study may provide metabolic connections between cell aging and biosynthetic capacity.